2005
DOI: 10.1590/s0100-29452005000200041
|View full text |Cite
|
Sign up to set email alerts
|

Influência da temperatura na germinação de sementes de Annona Montana

Abstract: Com o objetivo de avaliar a influência da temperatura sobre a porcentagem de germinação e o índice de velocidade de germinação (IVG) de sementes de Annona montana, conhecida como falsa graviola, espécie com potencial para porta-enxerto das variedades comerciais, testaram-se quatro temperaturas (20; 25; 30 e 35ºC). O trabalho foi desenvolvido em laboratório em câmaras de germinação tipo BOD, utilizando-se de sementes de três plantas provenientes do Banco de Germoplasma do Departamento de Produção Vegetal da Fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
3
5
0
5
Order By: Relevance
“…OLIVEIRA et al (2005) observed that the temperature causes effect both on the percentage of germination and germination speed index in Annona montana; also, the optimum temperature found for germination is around 30 °C, as can be observed in this study (Table 4).…”
Section: Resultssupporting
confidence: 83%
“…OLIVEIRA et al (2005) observed that the temperature causes effect both on the percentage of germination and germination speed index in Annona montana; also, the optimum temperature found for germination is around 30 °C, as can be observed in this study (Table 4).…”
Section: Resultssupporting
confidence: 83%
“…Experiments show and evidence the differentiated response according to the species, and Lamarca et al (2011) observed a wide adaptation to the emergence of seeds of some species of Eugenia in the most diverse temperatures tested, with germination and development of normal seedlings in the temperature range of 20 to 30ºC, being still indifferent to the temperature alternation (20/30 and 20/35ºC) and also reported by Lima et al (2007), who found higher rates for 'urucuzeiro' seeds at temperatures of 25, 30ºC and alternated between 20-30ºC. Silva et al (2006) observed better results for 'bacabinha' seeds when submitted to a temperature of 30ºC the same was verified by Oliveira et al (2005) for false annona muricata and by for 'jabuticabeira'. In each column, for each factor, averages followed by the same capital letter do not differ from each other by the "Tukey test", at 5%…”
Section: Sowing and Storage Testsupporting
confidence: 65%
“…OLIVEIRA et al (2005) estudaram sementes de sapota-preta (Diospyros ebenaster) e também observaram germinação em temperaturas constantes de 20, 25 e 30ºC e alternada de 20-30ºC, com maiores resultados a 30ºC.…”
Section: Resultsunclassified